Microbiota-derived short-chain fatty acids in hematopoietic stem cell transplantation: immunomodulation at the host-microbiota interface - Hajjar, Crystel; Kuijper, Ed J.; Butel, Marie-José; Khoury, Gaelle; Mallah, May; Karam Sarkis, Dolla; Lesnik, Philippe; Le Goff, Wilfried; Bazarbachi, Ali; Abifadel, Marianne (Frontiers in Microbiology, 2026)
Hematopoietic stem cell transplantation (HSCT) remains a cornerstone treatment for many hematological malignancies, but its clinical success is still challenged by graft-vs.-host disease (GvHD), infectious complications, and the profound microbial disruptions caused by conditioning, antibiotics, and hospitalization. Over the past few years, a growing body of work has highlighted how tightly post-transplant immunity is linked to the state of the gut microbiota. In particular, short-chain fatty acids (SCFAs), especially butyrate, have emerged as key microbial metabolites involved in maintaining epithelial barrier function, moderating inflammatory responses, and supporting regulatory T-cell homeostasis. In this review, we bring together current evidence on the SCFA-gut-immune axis in the setting of HSCT, with a focus on how transplant-related dysbiosis alters SCFA availability and contributes to immune imbalance. We also discuss the potential of strategies designed to restore or enhance SCFA production, ranging from dietary fiber interventions to next-generation probiotics and other microbiota-directed approaches. Overall, by better understanding and eventually harnessing the metabolic capacity of the gut microbiota, SCFA-centered therapies may offer new opportunities to support immune recovery, reduce GvHD risk, and improve outcomes for HSCT recipients. Still, well-designed clinical trials are needed to determine how these approaches can be safely and effectively integrated into transplant care.